Cross-age Peer Mentoring to Enhance Resilience Among Low-Income Urban Youth Living in High Violence Chicago Communities, 2014-2019 - Richards, Maryse ([Verlag nicht ermittelbar], 2021)
The goal of this mixed-methods study was to evaluate the effectiveness of community based cross-age mentoring to reduce negative outcomes related to violence exposure/engagement and promote positive development among African-American and Latinx youth from multiple sites serving four low-income, high violence urban neighborhoods, using youth mentors from the same high-risk environment. The program was named by youth mentors, "Saving Lives, Inspiring Youth" (or SLIY henceforth). Cross-age peer mentoring programs promise to solve problems and ineffectiveness of other types of mentoring programs, but few have been systematically studied in high-poverty, high-crime communities. In collaboration with several community organizations, a prospective approach was implemented to follow cross-age mentors and mentees for up to one year of mentoring. Both quantitative and qualitative methods were employed to examine possible changes in a number of relevant constructs, and to understand program impact in greater depth. Mentoring sessions lasting one hour took place each week, with an hour debriefing session for mentors following each mentoring session. Quantitative data were collected pre, post and at a 9-12 month follow-up. Throughout the mentoring intervention, several forms of qualitative data were gathered to make it possible for youth voices to permeate understanding findings, to illuminate program processes that youth perceived as helpful and not helpful, and to provide multiple perspectives on youths' resilience and their understanding of the risks they faced. Both mentors and community collaborators were trained and engaged as community researchers. School-based data were also collected. Demographic variables include participants' age, race, and grade in school.